SPEED OF ADJUSTMENT PADA STRUKTUR MODAL: ANALISIS BERDASARKAN SIKLUS HIDUP PERUSAHAAN DI INDONESIA - CICILIA SUSILAWATI; ROSALINA WIJAYANTI; CYRILLIUS MARTONO (Jurnal Bisnis dan Akuntansi, 2020)
At each stage of the life cycle, companies use different considerations to determine capital structure decisions. This study analyzes differences in company speed of adjustment towards optimal capital structure, based on the company's life cycle in Indonesia. The sample used 74 manufacturing companies from 2013 to 2017. The result is that the maturity company has a greater speed of adjustment than the introduction stage company. While the speed of adjustment at the growth stage there is no difference with the speed of adjustment at the introduction stage. Other findings in this study, the distance between the optimal capital structure and the realized capital structure reduces the difference in speed of adjustment at the maturity and introduction stages. So the conclusion is the company's life cycle becomes a determinant of capital structure decisions